Penerapan Terapi Stimulasi Sensori Terhadap Kemampuan Pasien Mengontrol Perilaku Kekerasan Pada Pasien Skizofrenia - Ayu Okta Viana; Norman Wijaya Gati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Schizophrenia is a disease that affects various areas of individual functioning, including thinking, communicating, receiving, interpreting reality, feeling, and showing emotions. Based on data from 32% of schizophrenics who commit acts of violence, and 16% of violent behavior towards clients results in death. One of the treatments that can be done is Sensory Stimulation therapy which is an effort to stimulate all the five senses (sensory) in order to provide an adequate response so as to increase the ability to control violent behavior in schizophrenic patients. schizophrenia Method: applying sensory stimulation therapy applied to 2 patients in the form of a case study. Results: The results showed that there was an increase in the patient's ability to control violent behavior which resulted in an increase in the score of the ability to control angry behavior by 10 and 9 points. Conclusion: Based on the data generated by the two patients, after the sensory stimulation therapy strategy was carried out, the risk of violent behavior decreased. With different amounts but with the same treatment.